Understanding poor lymphatic function and how to improve it: revisiting old facts and examining new leads to help wounds heal - Piller, Neil (Henry Stewart Talks, 2014)
Lymphoedema and oedema: key differences, Blood-tissue-lymph systems and their interfaces, Importance of the lymphatic system, Organization of superficial lymph system, Functioning of the lymphatic system, Consequences of poor lymph flow, Deep and superficial systems, The adipo-lymphatic connection, Fats in the diet: How they affect lymph flow and load, Lymphatic drainage from the small intestine, Blockage/overload and chylous reflux, Factors which determine lymph load and flow, Development of lymphoedema, Types of lymphoedemas, Increased subcutaneous fat reduces lymph transport, Build-up of fibrous tissues reduces lymphatic function, The problems of fibrosis, Proximity issues, Other limb swellings which look like lymphoedema which may underlie the wound area: Lipoedemas, Myxoedema and Phlebo-lymphoedema, Adipose tissue, fibrosis and lymphoedema, What can be done to improve tissue/cell health and improve wound healing?, Update interview: Use of Indocyanine green to visual functional lymphatics, Update interview: Use of objective measurements to ensure sequenced and targeted treatment, Update interview: Importance of patient empowerment
Updated at 2023/07/10